Anatomical localization of motor entry points of flexor digitorum superficialis - Theresa Susan Kuriakose; Mythraeyee Prasad; Sunil Jonathan Holla (Asian Journal of Medical Sciences)
Background: The knowledge about dense zones of motor entry points (MEPs) of muscles commonly involved in spasticity will be helpful for clinicians to inject the neurolytics into the ideal site.